STUDENT LEARNING ACTIVITIES IN SENIOR HIGH SCHOOL WHEN USING WORKSHEET BASED ON WEB MATTER KINGDOM ANIMALIA - PINASTHIKA, CININTA (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Abstract-Competency standards to be achieved in studying the kingdom Animalia is students must understand the benefits of biodiversity, and basic competencies is students are able to describe the characteristics of members of the animal world and the role to life. Achievement of these competencies requires observing skills or observe, identify morphological features, and classify animals based on common characteristics, instead of memorizing the the scientific names. So it developed a worksheets based on Web matter kingdom Animalia. This study aimed to describe the student activity when using worksheets Based on Web Matter Kingdom Animalia. Student activity observed with instruments observation of students during learning activities follow the existing procedures in the worksheet. Results of this study indicate students can follow the procedure on worksheets that includes observation, identifying and classifying, and found the concept. keywords: aktifitas siswa, keterampilan berpikir kritis, LKS berbasis Web. Kingdom animalia